Solving ordinary differential equations by the Dormand Prince method - Ang, Tau Keong; Amir Hamzah, Nor Shamsidah (Penerbit UTHM, 2018)
In general, differential equations in mathematics can be defined as an equation that comprises of one or more functions and its derivatives. Meanwhile ordinary differential equation in mathematics is declared as differential equations that contains one or more functions of one independent variable and its ordinary derivatives. Unlike partial differential equations, ordinary differential equations involve only the ordinary derivatives with respect to one independent variable. This research was conducted to solve ordinary differential equations by a numerical method called the Dormand Prince method. Consequently the solutions obtained are compared with the other numerical method in terms of accuracy. Dormand Prince method is one of the similar methods as RungeKutta method. It is used to solve an ordinary differential equation explicitly by six function evaluations. Throughout this research, the accuracy of the Dormand Prince method in solving ordinary differential equations was examined by comparing it with the other numerical method, which is Runge Kutta Fehlberg method.